Observation of the Impacts of the 2022 and 2025 Rainfalls on the Urban Drainage Infrastructure in Franco da Rocha, São Paulo - Pinto , Nathalia da Mata Mazzonetto; Silva , Alessandra Pereira (ANAP Brazil, 2025)
ABSTRACT Objective – This article aims to analyze the urban impacts resulting from heavy rains in the municipality of Franco da Rocha in 2022 and 2025, by comparing the scenarios observed before and after the implementation of the EU-09 reservoir, assessing the effectiveness of this infrastructure in the face of the increasing frequency of extreme weather events. Methodology – The research was developed using a methodology based on real and comparative data, based on the analysis of rainfall indices, photographic records, satellite images, and information on flooding obtained from official sources. The choice of events took into account technical and temporal criteria, and the data was integrated to assess the effects of the infrastructure implemented. Originality/Relevance – The study’s relevance lies in the current scenario of macro-drainage interventions in response to heavy rainfall, especially considering the intensification of extreme events related to climate change. Therefore, the municipality of Franco da Rocha, which has historically been frequently vulnerable to flooding, is also justified. Results – Although the EU-09 reservoir contributed to mitigating flooding in some parts of the city, it was not possible to prevent flooding in the central region of Franco da Rocha, highlighting the need for additional measures. Theoretical/Methodological Contributions – The work presents a quantitative analysis through hydrographs, as well as a qualitative analysis through the analysis of satellite images and photographic records. Social and Environmental Contributions – The study highlights the need for analyses incorporated into urban planning, considering not only structural interventions, but also territorial, social and hydrological aspects.